Climate change impacts on coastal soil and water management - Haj-Amor, Zied; Bouri, Soukra (Boca Raton, FL : CRC Press/ Taylor & Francis Group, 2020)
"Climate Change Impacts on Coastal Soil and Water Management discusses the latest approaches for monitoring soil and water degradation in coastal regions under current climate conditions and as well as potential further changes in the future. It presents an overview of climate change impacts on soil and water resources and summarizes the adaptation of practical options and strategies to minimize the potential risks, such as land degradation, and seawater intrusion. Presents the general properties and analysis of soil and water resource conditions for numerous coastal regions. Offers practical advice for adapting to climate change through case studies from diverse coastal settings around the globe. Presents information in an accessible format for practitioners in soil and water sciences, as well as for those working in related disciplines Includes end-of-chapter summaries assessing key areas. Written primarily for soil, water, agricultural, and environmental scientists, this book provides the latest research on soil and water resources management, soil processes and properties, and the related effects of climate change. It assesses the effectiveness of the conservation practices currently in use and under future climate change scenarios as well"--
OCLC-licensed vendor bibliographic record.
Keywords: Shore protection; Coast changes; Soil erosion -- Climatic factors; Coastal zone management; Climatic changes; LAW / Environmental; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Environmental Engineering & Technology